Case Report: Crosstalk between systemic lupus erythematosus and sickle cell syndromes—two cases from eastern India - Das, Dhriti Sundar (Frontiers in Lupus, 2024)
Autoimmune diseases and sickle cell abnormalities have been reported to share some common pathogenic pathways. Here, we describe two cases of individuals with sickle cell trait (SCT) who presented with antibodies to antinuclear antigens and clinical features consistent with systemic lupus erythematosus (SLE). These patients were from the eastern state of India, i.e., Odisha. Both patients had documented sickle cell trait and tested positive for anti-double-stranded DNA antibodies. They presented with lupus nephritis without any obvious features of sickle cell hemoglobinopathies. Crosstalk between SLE and SCT may explain this association, which needs validation in future large-scale studies.